Effects of non-dissolved redox mediators on a hexavalent chromium bioreduction process. Issue 2 (3rd March 2016) - Lian, Jing; Hu, Zhenzhen; Li, Zifu; Guo, Jianbo; Xu, Zhifang; Guo, Yankai; Li, Min; Yang, Jingliang
ABSTRACT: The effects of six non-dissolved redox mediators (RM) immobilized in cellulose acetate beads on enhancing Cr(VI) reduction by Mangrovibacter plantisponsor CR1 were investigated. In addition, the voltammetric behaviours and electron transfer capacities of the redox mediators were examined using electrochemical methods. Compared to the control beads, the Cr(VI) bioreduction rate with 1-chloroanthraquinone cellulose acetate beads (1-CAQ/CA beads) was increased up to 4.5-fold, which was mainly attributed to enhanced electron transfer by 1-CAQ. The redox mediators also improved the oxidation–reduction potential values of the Cr(VI) bioreduction processes, which might assist in Cr(VI) bioreduction. The role of the redox mediators was discussed based on the cyclic voltammetric characteristics ( E 0 ') of the redox mediators and the electrochemical impedance spectroscopy characteristics ( R ct ) of the RM/CA beads. A linear correlation was found for the reaction constant k and the 1-CAQ concentration ( C 1-CAQ ), which was k = 1.5674 C 1-CAQ + 4.8506 ( R 2 = 0.9683). The Cr(VI) bioreduction was affected by temperature, and the optimum pH for the Cr(VI) bioreduction was 6.5. The results of repeated-batch operations showed that 1-CAQ/CA beads exhibited good stability and persistence. This study contributes to a better understanding of the effects of the redox mediator on Cr(VI) bioreduction process and demonstrates its promising potential for environmental bioremediation applications.